Whiteness under threat: Farmlands and the construction of whiteness in its YouTube comment space - Kelly, Megan (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
This study examines how whiteness, particularly South African whiteness, is constructed in a propagandistic YouTube documentary entitled Farmlands and how these constructions are taken up and negotiated by its viewers in its associated comment section. I suggest that these constructions are not only racialised, but resuscitate and popularise old colonial discourses that perpetuate the fear of a 'white genocide' and the perceived extermination of a 'pure white civilisation'. A thematic analysis informed by theories of representation, the establishment of difference through meaning, discourse and critical whiteness studies show that there are several narratives constructed through binary oppositions informed by colonial understandings of race, juxtaposing whiteness and blackness. In analysing these constructions, I aim to demonstrate that whiteness often becomes violent and defensive when its power is perceived to be under threat, reproducing itself through binary constructions that aim to protect it. In doing so, I demonstrate how whiteness is globalising from previous narrow nationalist framings to embracing a globalised notion of 'white civilisation under threat'. This study supports research that is sceptical of the democratizing ability of the internet and social media, focusing specifically on YouTube's comment forum and how it is utilized to mobilize attitudes based on hatred, racism and profound social exclusion.
Keywords: Farmlands (Documentary); YouTube (Firm); Mass media and propaganda -- South Africa; Afrikaners -- South Africa -- Attitudes; Propaganda, -- South African; Farmers -- Violence against -- South Africa; Racism in mass media; Whites -- Race identity -- South Africa